The negative impact on the audit process in health services due to the deficit of nursing records (Research, Society and Development, 2022)
AbstractIntroduction: In nursing, auditing seeks to thoroughly identify information that is recorded in patients' charts, thus seeking to evidence quality of care and cost control. Objective: to analyze the scientific production regarding the impact on the auditing process in health services by the absence or failures of nursing records as a measure of the quality of nursing care. Results/Discussion: 10 articles were selected.The nurse has gained autonomy to carry out the audit process in the institutions together with other sectors, aiming to identify a priori the quality of the care provided to the patient and to orient as to the deficits occurring during this process, providing estimated data for improving the quality of care. Final considerations: the importance that auditing has within healthcare institutions is well known, aiming to be an effective measurer in the process of patient care and good billing management. Keywords: "Nursingaudit"; "Nursing processes"; "Nursingrecords".